Output Feedback Sliding Mode Control of PEM EL-IBC System for Hydrogen Production. Issue 29 (2019) - Koundi, M.; Fadil, H. El; Rachid, A.; Idrissi, Z. El; Giri, F.; Guerrero, J.M.
Abstract: This paper deals with the problem of controlling an interleaved buck converter (IBC) associated with a Proton Exchange Membrane Electrolyzer (PEM-EL) used in electrical energy storage applications. The control objective is to regulate the electrolyzer voltage to its reference and to ensure an asymptotic stability of the closed loop system. The point is that the internal voltage of the double layer charge capacitor of the electrolyzer is not accessible for measurement. So, an output feedback controller, combining an observer and a sliding mode controller (SMC), is developed. The observer is also used to estimate all inductor currents of the IBC making the solution cheaper and more reliable. It is shown using a formal analysis and numerical simulations, that the proposed output feedback controller meets all control objectives.